Изучение декатионизирования ширакского морденита методaми дериватографического и газохроматографического анализов - Ф. А. Григорян; А. М. Калпакян; Н. Б. Князян; А. А. Маргарян (ՀՀ ԳԱԱ հրատ.)
В работе исследовано влияние декатионизирования в результате обработки ширакского морденита Армении соляной кислотой в течение 2 и 6 ч на его дериватографические и газохроматографические свойства при адсорбции легких предельных углеводородов С1 ч С4. Установлено, что наиболее благоприятные условия разделения указанных углеводородов наблюдаются на адсорбенте, обработанном в течение 6 ч при температуре колонки 160 и 240˚С. Աշխատանքում հետազոտված է ապակատիոնացման ազդեցությունը 2 և 6 ժ տևողությամբ աղաթթվով մշակված Շիրակի մորդենիտի հատկությունների վրա` թեթև սահմանային ածխաջրածինների ադսորբցիայի դեպքում: Պարզվել է, որ C1÷C4 ածխաջրածինների առավել հարմար բաժանման պայմաններ դիտվում են երկրորդ ադսորբենտի վրա քրոմատոգրա‎ֆիկ սյան 160 և 2400C պայմաններում: The influence of decationization аnd dehydration of Shirak natural mordenite (Armenia), being pretreated by hydrochloric acid 2 and 6 h, as depended upon the adsorbtion of the normal-light-carbon-hydrides of C1C4 is investigated by DTGA and gaz-chromatographic methods. Water starts to remove from the pores of mordenite at 115÷240°C, as Gas-Chromatographic and DTGA studies of mordenite shows, treated 6 h by hydrochloric acid. The rest of the water fully leaves at 680°C. The water maximal removal temperature tends to decrease upon increasing the mordenite treatment duration by HCl. Cation-water dipole molecule interaction weakens thus easing dehydration thanks to decationization of mordenite. Normal-light-carbon-hydrides C1÷C4 are adsorbed on the decationized and water-free surface of mordenite by the Van der Waales interaction forces. he optimal conditions of separation of on pretreated adsorbent were established for 160 and 240°C column temperatures and rate of gas-currier 32 ml per min.
Keywords: Inorganic Chemistry